Ontologi: Membongkar Hakikat Keberadaan dalam Dunia Filsafat - Arum Berliana Prasanty; Darodjat Darodjat (Student Research Journal, 2024)
Science and knowledge are important things for every individual to have, which can help human in solving problems in daily life. Science has certain parts, there are object, statement, proposition, and characteristic. These four aspects are emphasized by the three foundations of philosophical thinking: ontology, epistemology, and axiology. Ontology is defined as a discipline that investigates what exactly things are. There are several theories from this school such as monoism, dualism, pluralism, nihilism, and agnosticism. The concept of existence in Islam is a coherent and comprehensive system, which provides an explanation of the nature of everything that exist. In the context of education, ontology discusses what exists in the world of education such as objects, concepts, and entities involved in the teaching and learning process. Keywords: , , ,